Problematika Kebahasaan Dalam Pernyataan Presiden Prabowo (29 Agustus 2025) Tentang Demonstrasi: Analisis Pragmatik Dan Retorika - Sari, Desi Novita; Musarofah, Musarofah; Subyantoro, Subyantoro; Rahayu Pristiwati (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Language holds significant symbolic power in shaping a leader’s political image. This study examines President Prabowo Subianto’s statement on August 29, 2025, regarding the demonstrations, from the perspectives of pragmatics and rhetoric, in order to reveal how language is used to manage discourse and reinforce governmental legitimacy. This research employs a qualitative descriptive method with content analysis of the official speech text. The findings show that the statement contains various linguistic issues, such as the use of authoritative diction, the presence of implicit and ambiguous meanings, and the balance between emotional and rational utterances. From a rhetorical perspective, the president employs ethos to affirm his image as a dignified and responsible leader; pathos to evoke public sympathy through expressions of condolence; and logos to demonstrate logical reasoning through promises of action and law enforcement. These strategies collectively construct a stable political discourse, yet also hold the potential for problems due to differing interpretations among the public. This study emphasizes that political communication in the context of modern governance cannot be separated from in-depth linguistic analysis, as language plays a crucial role in maintaining legitimacy and social stability. Therefore, greater pragmatic and rhetorical awareness is required in political communication so that national messages can be conveyed effectively, ethically, and contextually.